Implementasi Manajemen Pengelolaan Zakat Produktif Pada Badan Amil Zakat Nasional Kabupaten Langkat Periode Tahun 2022-2023 - Adelia, Syahfira; Sani, Abdullah; Hasanah, Nurul (Pusdikra Publishing, 2023)
The implementation of productive zakat management at the National Amil Zakat Agency (BAZNAS) of Langkat Regency is by providing multilevel business assistance with several levels or stages. Baznas conducts surveys and observations of prospective muzakis to obtain information on the eligibility to receive productive zakat. In addition, the implementation of productive zakat is carried out by providing entrepreneurship training to mustahik so that they have skills in managing a business. Productive zakat is also given in the form of scholarships to poor students and students so they can complete their education. Productive zakat also has positive and negative sides. On the positive side, the distribution of zakat with this model will provide benefits that are not only temporary. Because productive zakat focuses on the area of ??empowerment and development of mustahiq which is continuous and neatly and systematically controlled. While on the negative side, the impact cannot be felt directly and immediately. Because the productive zakat model tends to take longer to touch the spirit to develop and grow creative and empowered power for mustahiq. Productive zakat is believed to be an alternative source of funds for the economic empowerment of the poor. The problem really depends on the ability of Amil zakat institutions to collect, manage and utilize zakat funds. Amil zakat institutions are required to strengthen institutions, improve the quality of human resources at amil and complete the necessary regulations.